2000
DOI: 10.1053/ejvs.2000.1199
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention and Treatment of Vascular Graft Infection With a Triclosan (Irgasan®)-bonded Dacron Graft:an Experimental Study in the Pig

Abstract: in this animal model Triclosan bonding appears effective in preventing prosthetic graft infection. However, the in situ replacement of Triclosan-protected grafts was not successful in the treatment of graft infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Hernandez et al [10] reported that triclosan restricted infections well, but this solution was not applicable to the replacement of infected prostheses or high-level infections. In addition, triclosan is on the list of compounds known for their inducement of bacterial resistance, and therefore should not be authorized on implantable biomedical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Hernandez et al [10] reported that triclosan restricted infections well, but this solution was not applicable to the replacement of infected prostheses or high-level infections. In addition, triclosan is on the list of compounds known for their inducement of bacterial resistance, and therefore should not be authorized on implantable biomedical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Although the initial results seemed to confirm the usefulness of rifampicin-impregnated [13], silver-impregnated or triclosan-impregnated [14] grafts in the treatment of limited vascular prosthetic graft infections, larger studies have shown that the results of treatment with rifampicin-impregnated grafts are unsatisfactory in cases of MRSA, fungi and rifampicin-resistant Staphylococcus epidermidis. These infections were responsible for a 16%-35% mortality rate in studies by Bandyk et al [13] and Hayes et al [15].…”
Section: Discussionmentioning
confidence: 99%
“…The potential of such measures was demonstrated recently in vascular prosthetic grafts [9]. In this study, triclosan was bonded to a graft material, applied to the femoral arteries of 51 pigs, and the grafts infected with S. aureus (2 ϫ 10 7 colonyforming units/mL).…”
Section: S-66mentioning
confidence: 96%